2014
DOI: 10.1002/iroh.201301717
|View full text |Cite
|
Sign up to set email alerts
|

Do planktonic rotifers rely on terrestrial organic matter as a food source in reservoir ecosystems?

Abstract: We studied the effect of input of allochthonous organic matter on rotifers in a medium-sized (9.8 km 2 ) reservoir correlating rotifer abundance to values of d 13 C in a sestonic fraction of !10 mm. Total density of rotifers during the study period was significantly correlated with tributary inflow during the time preceding the sampling date, with a delay of about 10-13 days. Concomitant with elevated tributary inflow, the d 13 C value in the sestonic fraction of plankton samples decreased approaching a level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…A recent study by Wilk-Woźniak et al (2014) identified an increase in allochthonous resource use with availability, as promoted by reservoir inflow. The availability of both allochthonous and autochthonous organic matter in reservoirs is potentially controlled by seasonal factors (temperature, light, etc.)…”
Section: Variability In Resource and Consumer Allochthonymentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study by Wilk-Woźniak et al (2014) identified an increase in allochthonous resource use with availability, as promoted by reservoir inflow. The availability of both allochthonous and autochthonous organic matter in reservoirs is potentially controlled by seasonal factors (temperature, light, etc.)…”
Section: Variability In Resource and Consumer Allochthonymentioning
confidence: 99%
“…While the magnitude and importance of allochthonous inputs have been studied in both lakes and streams (Rasmussen, 2010;Cole et al, 2011;Marcarelli et al, 2011;Cole & Solomon, 2012;Roach, 2013), allochthonous resource use in reservoir food webs has received less attention (but see Babler et al, 2011;Wilk-Woźniak et al, 2014), although a recent study using stable isotopes identified a positive and nearly 1:1 relationship between zooplankton and POM d 13 C (Jeayong et al, 2013). Use of allochthonous resources by consumers in lakes is variable but tends to be correlated with allochthonous resource availability Wilkinson et al, 2013a;Berggren et al, 2014;Tanentzap et al, 2014;Berggren et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current supply of allochthonous POM may be more important to the reservoir's plankton community than the standing stock of available organic matter of autochthonous origin. Previous research on the planktonic food web of Dobczyce Reservoir has demonstrated the importance of allochthonous organic matter controlling the abundance of rotifers (Wilk‐Woźniak et al ., ). The greater importance of terrestrial POM for benthic invertebrates is probably restricted to areas close to tributary inflows, as shown by the δ 13 C values recorded in their vicinity and by the significant enrichment of 13 C in the benthos close to the dam.…”
Section: Discussionmentioning
confidence: 99%
“…Animals that feed on the seston and bacteria are an important link in the transfer of carbon from bacterial biomass to macrozooplankton [51, 52], and might compete with ciliates which also transfer organic matter from bacteria in a microbial loop. This possibility will be the focus of our future work.…”
Section: Discussionmentioning
confidence: 99%